A study of conceptual game design. - Cheah, Benjamin Han Boon. (2012)
The interactive and rule-based nature of the game medium gives it untapped potential for creating expressive and artistic works. Through the development of a conceptual game, I explored the challenges of the game making process and how the formal properties of the medium enable deeper meaning and representation in a conceptual work.